THE NEW WORLD SPECIES OF CINNAMOMUM TREW (LAURACEAE) - Kostermans, AJGH (REINWARDTIA, 1961)
The American species of Phoebe Nees are relegated to Cinnamomum Trew; the reasons for this transfer are discussed. To retain nomenclatural stability the new combinations which have become necessary are presented, in anticipation of a general revision of the genus Cinnamomum; 68 new combinations and names are presented.